Investigation of the influence of oceanographic parameters on coastal photovoltaic systems - Kazolis Dimitrios; Fantidis Jacob; Fotakis Christos Dionyshs; Roumeliotis Nikolaos (E3S Web of Conferences, 2025)
The global imperative to transition to renewable energy sources has made photovoltaic technology a key element in the implementation of sustainable energy strategies. The photovoltaic systems are solidly established because they offer a number of advantages, but their performance is strictly linked to the environmental conditions. In particular, coastal installations are confronted with a number of unfavourable conditions, such as humidity or saltiness of the air. This specific category is targeted by the present work. This paper is devoted to the effect that oceanographic conditions are likely to have on the performance of the specific systems. To investigate this purpose, annual data including both oceanographic and photovoltaic performance data are processed and analysed. Both statistical methods such as Factor Analysis and unsupervised learning processes such as k-means cluster analysis, are applied in order to draw correlations. Finally, the conclusions derived from the deployment of these procedures are presented in detail. The innovative part of this work lies not only in the implementation of the specific methodologies and the unsupervised learning approach, but mainly in the combination of the specific databases, which aims to bridge the gap that exists in the research on these specific issues.